Characteristics associated with residential aged care, respite and transitional aged care placement for older people following an injury-related hospitalisation in Australia. (2017) - Mitchell, Rebecca; Harvey, Lara; Draper, Brian; Brodaty, Henry; Close, Jacqui
No abstract available